Transformation of Syariah courts: Tradition, constitution, law and practice - Shuaib, Farid Sufian (2013)
In discussing about the administration of Islamic law in Malaysia, one could not avoid but to discuss Syariah courts since Malaysia has adopted the model of parallel court system in applying Islamic law. Not much materials could be found on the courts in existence in the early history of Malaysia. However, looking at the development of Syariah courts during the British colonization and afterwards, we could see transformation of Syariah courts.